HPMA-RGD hydrogels seeded with mesenchymal stem cells improve functional outcome in chronic spinal cord injury - Hejcl, Ales; Sedý, Jirí; Kapcalová, Miroslava; Toro, David Arboleda; Amemori, Takashi; Lesný, Petr; Likavcanová-Mašínová, Katarina; Krumbholcová, Eva; Prádný, Martin; Michálek, Jirí; Burian, Martin; Hájek, Milan; et al. (Stem cells and development, 2010)
Chronic spinal cord injury (SCI) is characterized by tissue loss and a stable functional deficit. While several experimental therapies have proven to be partly successful for the treatment of acute SCI, treatment of chronic SCI is still challenging. We studied whether we can bridge a chronic spinal cord lesion by implantation of our newly developed hydrogel based on 2-hydroxypropyl methacrylamide, either alone or seeded with mesenchymal stem cells (MSCs), and whether this treatment leads to functional improvement. A balloon-induced compression lesion was performed in adult 2-month-old male Wistar rats. Five weeks after injury, HPMA-RGD hydrogels [N-(2-hydroxypropyl)-methacrylamide with attached amino acid sequences--Arg-Gly-Asp] were implanted into the lesion, either with or without seeded MSCs. Animals with chronic SCI served as controls. The animals were behaviorally tested using the Basso–Beattie-Breshnahan (BBB) (motor) and plantar (sensory) tests once a week for 6 months. Behavioral analysis showed a statistically significant improvement in rats with combined treatment, hydrogel and MSCs, compared with the control group (P < 0.05). Although a tendency toward improvement was found in rats treated with hydrogel only, this was not significant. Subsequently, the animals were sacrificed 6 months after SCI, and the spinal cord lesions evaluated histologically. The combined therapy (hydrogel with MSCs) prevented tissue atrophy (P < 0.05), and the hydrogels were infiltrated with axons myelinated with Schwann cells. Blood vessels and astrocytes also grew inside the implant. MSCs were present in the hydrogels even 5 months after implantation. We conclude that 5 weeks after injury, HPMA-RGD hydrogels seeded with MSCs can successfully bridge a spinal cord cavity and provide a scaffold for tissue regeneration. This treatment leads to functional improvement even in chronic SCI.
Keywords: náhodné rozdělení; methakryláty; chování zvířat; experimentální implantáty; Humans; poranění míchy; Spinal Cord; Oligopeptides; hydrogely; Mesenchymal Stem Cell Transplantation; Chronic Disease; mícha; Spinal Cord Injuries; krysa rodu Rattus; výsledek terapie; lidé; zvířata; Nerve Regeneration; oligopeptidy; regenerace nervu; potkani Wistar; transplantace mezenchymálních kmenových buněk; Rats, Wistar; Male; mezenchymální kmenové buňky; chronická nemoc; Treatment Outcome; Hydrogels; Rats; Animals; mužské pohlaví; Methacrylates; Implants, Experimental; Random Allocation; Behavior, Animal; Mesenchymal Stem Cells